Pengaruh mikronutrien taburia terhadap perkembangan motorik anak usia 24-48 bulan yang stunting (Studi di Tanjungkarang Barat Kabupaten, Bandar Lampung) - Nugroho, Arie; Susanto, Hardhono; Kartasurya, Martha Irene (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Stunting is associated to the developmental delays of gross motor and fine motor skills. Previous studiedstate that micronutrient supplementation has a positive effect on both motor skills development in children aged under24 months.Objective: The aim of this study was to analysis the effect of micronutrient sprinkle on motor development amongstunted children aged 24 to 48 months.Methods: A quasi-controlled experimental group study with a total of 63 stunting age 24-48 months are divided intotreatment group (31 children) and controls (32 children). Treatment group received micronutrient sprinklesupplementation once in two days for two months. Fine and gross motor development was measured by DDST II beforeand after intervention.Results: There was no difference in age, sex, energy intake, protein, zinc, folic acid and developmental delaypercentage before treatment. The percentage of fine motor delays before treatment was 48.4% in the treatment groupand 53.1% in the control group, while the percent of gross motor delay was 32.3% in the treatment group 34.4% in thecontrol group. After intervention, the percentage of fine motor developmental delays significant decreases 25.8%, in thetreatment group and 34.4% in the control group, while the percentage of gross motor delay in the control groupsignificant decreased to 12.5%, but not significant decreased to 16,1% in the treatment group. Confounding variablesin this study were include energy adequacy level, protein adequacy level, zinc, iron and folic acid. There was nodifferences percentage of developmental delays on fine motor (p= 0,514) and gross motor (p= 0,571) after theintervention and after controlling with confounding variables.Conclusion: Micronutrient sprinkle supplementation for two months did not influence the development of fine motorskills gross motor skills on stunting preschooler children age 24 to 48 months